Pengaruh Iklim Sekolah yang Dimoderating oleh Supervisi Akademik terhadap Mutu Sekolah di SMA - Shelvie Famella; Sufyarma Marsidin; Rifma Rifma (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The purpose of this study was to analyze the significant influence of pedagogical competence and school climate influenced by academic supervision to the quality of SMA Negeri 8 in Pekanbaru City. The sample of this research is 80 respondents taken with a proportional random sampling technique. Data collection in this research was done through questionnaire dissemination. Data analysis used is descriptive analysis, inferential statistical analysis and hypothesis testing. Hypothesis test using simple linear regression and Moderated Regression Analysis (MRA). The reliability coefficient of the instrument is calculated using Cronbach's alpha formula. The result of the research shows pedagogic competence (X1) affect the quality of school (Y) equal to 20,3%, school climate (X2) influence school quality (Y) equal to 10,8%, pedagogic competence (X1) moderated academic supervision variable (Z) affecting the quality of school (Y) of 33.3%, school climate (X2) moderated academic supervision variable (Z) affect the quality of school (Y) of 25.4%, pedagogic competence (X1) and school climate (X2) moderated supervision variable academic (Z) affect the quality of school (Y) equal to 28,7%.